Lakum dīnukum wa-liya dīnī: Acehnese Attitudes Toward Interfaith Relations - Safira Indah (Yayasan Bayt Shufiya Nusantara, 2024)
This study aims to examine how Acehnese people, especially in Tanah Merah Village, Southeast Aceh District, build and maintain inter-religious relations in daily life. Through a qualitative approach, data were collected naturally through observation, in-depth interviews, and documentation involving non-Muslim communities, village officials, and Islamic religious leaders. Data analysis was conducted using triangulation method and sociology of religion approach, to understand the social dynamics and interfaith relations that develop. The findings show that the principle of “lakum dīnukum wa-liya dīnī” is not merely a normative teaching, but is translated into social ethics in the form of respect for religious freedom, maintaining order during worship, and harmonious interfaith communication. This study recommends the importance of maintaining local values and social wisdom in strengthening the cohesion of a multicultural society.